Cholinergic Submucosal Neurons Display Increased Excitability Following in Vivo Cholera Toxin Exposure in Mouse Ileum - Fung, Candice; Koussoulas, Katerina; Unterweger, Petra; Allen, Andrew M.; Bornstein, Joel C.; Foong, Jaime P. P. (Frontiers in Physiology, 2018)
Cholera-induced hypersecretion causes dehydration and death if untreated. Cholera toxin (CT) partly acts via the enteric nervous system (ENS) and induces long-lasting changes to enteric neuronal excitability following initial exposure, but the specific circuitry involved remains unclear. We examined this by first incubating CT or saline (control) in mouse ileal loops in vivo for 3.5 h and then assessed neuronal excitability in vitro using Ca2+ imaging and immunolabelling for the activity-dependent markers cFos and pCREB. Mice from a C57BL6 background, including Wnt1-Cre;R26R-GCaMP3 mice which express the fluorescent Ca2+ indicator GCaMP3 in its ENS, were used. Ca2+-imaging using this mouse model is a robust, high-throughput method which allowed us to examine the activity of numerous enteric neurons simultaneously and post hoc immunohistochemistry enabled the neurochemical identification of the active neurons. Together, this provided novel insight into the CT-affected circuitry that was previously impossible to attain at such an accelerated pace. Ussing chamber measurements of electrogenic ion secretion showed that CT-treated preparations had higher basal secretion than controls. Recordings of Ca2+ activity from the submucous plexus showed that increased numbers of neurons were spontaneously active in CT-incubated tissue (control: 4/149; CT: 32/160; Fisher’s exact test, P < 0.0001) and that cholinergic neurons were more responsive to electrical (single pulse and train of 20 pulses) or nicotinic (1,1-dimethyl-4-phenylpiperazinium (DMPP; 10 µM)) stimulation. Expression of the neuronal activity marker, pCREB, was also increased in the CT-treated submucous plexus neurons. c-Fos expression and spontaneous fast excitatory postsynaptic potentials, recorded by intracellular electrodes, were increased by CT exposure in a small subset of myenteric neurons. However, the effect of CT on the myenteric plexus is less clear as spontaneous Ca2+ activity and electrical- or nicotinic-evoked Ca2+ responses were reduced. Thus, in a model where CT exposure evokes hypersecretion, we observed sustained activation of cholinergic secretomotor neuron activity in the submucous plexus, pointing to involvement of these neurons in the overall response to CT.